KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DIKAJI DARI SELF CONFIDENCE - Tjut Aflianti Eka Putri; Yulis Jamiah; Sivia Sayu (Jurnal AlphaEuclidEdu, 2020)
The purpose of this research is to describe the mathematical communication skills of students assessed from self confidence in the material system of two-variable linear equations in SMP Muhammadiyah 1 Pontianak.  The method in this research is descriptive research method with survey research. The sample of the research were the students of IX A SMP Muhammadiyah 1 Pontianak.  Research subjects were 28 students. From the results of the self confidence questionnaire, obtained data of 6 students having a low level of self confidence and 22 students having a high level of self confidence.  In addition to administering questionnaires, students were also given mathematical communication skills test and interview questions.  From the results of tests and interviews obtained written mathematical communication skills of subjects with low levels of self confidence can fulfill one of the four indicators of mathematical communication skills.  While the verbal mathematical communication skills of subjects with low self confidence levels can fulfill two of the four indicators of mathematical communication skills.  In addition, subjects with high levels of self confidence can fulfill all indicators of mathematical communication skills both in writing and verbal.Keywords: Mathematical Communication, Self Confidence